MENINGKATKAN LITERASI SISWA TERHADAP PRIVASI DAN KEAMANAN DATA SERTA PENGENALAN UU ITE: Improving student’s Literation on privacy, data security and introduction of ITE Laws - Saut Pintubipar Saragih; Mesri Silalahi; Irene Svinarky (ASOSIASI IDEBAHASA KEPRI, 2023)
Last decade has been enormosly rapid growt of technology development in all areas of industries in the world including private data into the technology in its core system or application. The importance of data and information security is getting crucial amid the information era, those are done so to enhance the security of technology and electronic transactions users getting more control to their data and information to a higher level of security. These data protection efforts are no exception to the data and information owned by students or participants. Community service activities targeted by the school that have been carried out several times have a positive impact on both the school, especially for the student. The result of this event is achieved that measured with the enthusism from the participants during the Lectures. The result shows the comprehensive of understanding among the student increased related to the privacy and security aspects. They have better expertise in securing personal data and information and generate the harmless action in internet activity tha leas to harming the participants also related to information and telecommunication technology or ITE. Aspect of knowledgein ITE Laws in Indonesia was so important as participant aware of their action has to be manages as the proportion of normality during their internet usage as well.